TRENDS, POTENTIAL AND CHALLENGES OF HLI’s LEADERSHIP DURING COVID-19 PANDEMIC - Romzi Ationg; Mohd Sohaimi Esa; Mohd Azri Ibrahim; Mohd Kamal Mohd Shah; Muhammad Safuan Yusoff; Irma Wani Othman; Saifulazry Mokhtar (Journal of Islamic, Social, Economics and Development, 2021)
The outbreak COVID-19 pandemic plays a significant impact on the functional of Higher Learning Institutions (HLIs) globally. This is especially true in the area of leadership. But what exactly are the impacts of Covid-19 pandemic on HLI’s leadership? To understand the impacts of Covid-19 pandemic on HLI’s leadership, exploring the trends, potentials and the challenges associated with the issue is immensely valuable. Accordingly, by applying a qualitative approach through the examination of information gathered from various sources such as books, journals and media reports, the paper presents a discussion on trends, potential and challenges of Higher Learning Institution’s (HLI) Leadership during Covid-19 pandemic. The paper is expected to contribute in the understanding of trends, potential and challenges of Higher Learning Institution’s (HLIs) Leadership during Covid-19 pandemic, thus led to the improvement of HLI’s leadership despite the pandemic.